William Duval (1858-1931) - Harper, Kenn (ARCTIC, 1985)
. At the age of 21, William Duval shipped aboard a whaler for the Arctic; he arrived in Cumberland Sound in the summer of 1879 and remained there for the next four years. He was usually employed as second helmsman aboard the Lizzie P. Simmonds, a whaler owned by an American firm, Williams and Company. In 1883 he returned to the United States for a year. His activities over the next 20 years are little known. . In the Arctic, Duval lived a life not unlike that of the Inuit whom he came to know so intimately. He learned to speak their language fluently, and they gave him an Inuktitut name - Sivutiksaq, the harpooner. He married a native woman, Aullaqiaq. They had at least four children. . In 1903 Duval and his family, with other Cumberland Sound Inuit, accompanied the Scottish whaler James Mutch to Pond Inlet to establish the first shore station there for Robert Kinnes's Dundee-based whaling and trading firm. Duval remained in northern Baffin Island until 1907, when he returned to the United States for a winter. The following year he went out again and for the next eight years ran a post for Kinnes at Durban Harbour on the Baffin coast of Davis Strait. In 1916 he joined Henry Toke Munn's Arctic Gold Exploration Syndicate, despite its name a fur-trading company; he and his family accompanied Munn to Southampton Island, where they traded for two years. Duval returned to Cumberland Sound in 1918 and established a post for Munn at Usualuk, the American Harbour of the whalers. He remained there until 1922; in that year he returned to the United States again and spent the winter with relatives in New Jersey. The following year the Canadian government employed Duval as interpreter for the trial at Pond Inlet of the Inuit charged with the murder of the trader Robert Janes, the first trial in the High Arctic. In interpreting the words of the judge and the verdict of the jury against the three Inuit accused, Duval, a man who had long straddled two immensely different cultures, felt an empathy for the Inuit who could not ...